2016
DOI: 10.1007/s10903-016-0528-6
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment Linked with a Deterioration of Psychosocial Outcomes in Adult Life for Southern Brazilian Transgender Women

Abstract: A history of childhood maltreatment (HCM) has been associated with detrimental psychiatric outcomes. This is particularly true for transgender, for whom there is initial evidence that HCM may be associated with psychiatric morbidity. Our study aimed to further characterize the relationship between HCM and the development of mental disorder in adult life, based on a sample of Brazilian transgender women. Cross-sectional data were collected from a consecutive sample of 289 transgender women who attended the Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
12
0
1
Order By: Relevance
“…81,82 Additionally, a recent metanalysis revealed that physical and sexual abuse is linked with increased risk for depression and anxiety in adulthood. 83 In this regard, our group has found that a quarter of individuals with GD experienced some degree of childhood maltreatment, 61 and it was associated with psychiatric disorder, suicide risk and worse psychosocial outcomes, such as sex work and unemployment, in adult life. In contrast, Bandini et al found that childhood maltreatment in transsexual women was not only linked to psychiatric comorbidity, but also to body dissatisfaction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…81,82 Additionally, a recent metanalysis revealed that physical and sexual abuse is linked with increased risk for depression and anxiety in adulthood. 83 In this regard, our group has found that a quarter of individuals with GD experienced some degree of childhood maltreatment, 61 and it was associated with psychiatric disorder, suicide risk and worse psychosocial outcomes, such as sex work and unemployment, in adult life. In contrast, Bandini et al found that childhood maltreatment in transsexual women was not only linked to psychiatric comorbidity, but also to body dissatisfaction.…”
Section: Discussionmentioning
confidence: 96%
“…59 In this regard, people diagnosed with GD are chronically exposed to stigma and prejudice, often reflected by exposure to traumatic events like physical and sexual violence, 60 and they experience a high prevalence of childhood maltreatment. 61 There is evidence that being under such stressors may contribute to the onset of psychiatric comorbidities in the future. In addition, it has been considered that imbalanced inflammatory cytokine levels are linked to childhood maltreatment and that this imbalance plays a role in the development of mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Survival sex work is a term that has been promulgated to identify sex exchanged for money or other commodities as a means of basic subsistence (Shannon et al, 2007). As we described elsewhere (Fontanari et al, 2018), the choice to engage in sex work must be understood in the context of a Brazilian nation where sex work is not criminalized but legislation prevents it from being institutionalized (pimping and specific houses for prostitution) (Bindman, 1997). It is unregulated and there are no support mechanisms or educational resources to ensure the safety of individuals who engage in the practice.…”
Section: Discussionmentioning
confidence: 99%
“…In general, transgender individuals report more mental health issues than their cisgender counterparts (Streed et al, 2018). According to an investigation carried among transgender women in Brazil, there was a "high prevalence of psychiatric diagnosis, including psychoactive drug use, suicide attempts, major depressive disorder, psychoses, social phobias, and obsessive-compulsive behavior" (Fontanari et al, 2018). In the United States, 57% of transgender individuals have reported experiencing depression, and 42.1% have reported anxiety.…”
Section: Mental Healthmentioning
confidence: 99%